Computer-Assisted Cognitive Remediation in Schizophrenia: Efficacy of an Individualized vs. Generic Exercise Plan - Bossert, Magdalena; Westermann, Celina; Schilling, Thomas M.; Weisbrod, Matthias; Roesch-Ely, Daniela; Aschenbrenner, Steffen (Frontiers in Psychiatry, 2020)
Computer-assisted cognitive remediation (CACR) is an economical, adjustable, and effective treatment for individuals with schizophrenia. The current randomized controlled study examined whether an individualized or generic exercise plan in CACR is superior in patients with multiple cognitive deficits compared to treatment-as-usual (TAU). Fifty-nine inpatients diagnosed with schizophrenia were randomly assigned to 1) TAU, 2) TAU plus an individualized exercise plan in CACR, or 3) TAU plus a generic exercise plan in CACR. Neuropsychological performance, psychopathology, and functional outcome were assessed at baseline and post-treatment. The results show a medium to large training effect for all neuropsychological performance measures. Contrary to our expectations the neuropsychological improvement over time did not differ between groups. Self-reported depression, global level of functioning, and activity and participation functioning showed a significant improvement from baseline to post-treatment. However no further group, time, or interaction effects for other psychopathology and functional outcome could be demonstrated. Possible implications for clinical use of CACR and future studies are discussed.